Development of the Gulamo River Tourism Object XIII Koto Kampar District Kampar Regency - fitrawan adrian; Zulkarnaini Zulkarnaini (PAJ, 2021)
Development of the Gulamo River Tourism Object XIII Koto Kampar District Kampar Regency